EVALUASI IMPLEMENTASI PAJAK PROGRESIF TERHADAP KENDARAAN BERMOTOR DI KABUPATEN MINAHASA UTARA PROVINSI SULAWESI UTARA - Adiputra, Mandang; Karamoy, Herman; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Motor vehicle tax is a potential tax in local revenue. Progressive tax on motor vehicles is valid from January 2012 in North Sulawesi based on the implementation of the Provincial Regulation No. 7 of 2011 on Regional Taxes. The purpose of this study is to know the implementation of progressive tax on motor vehicles in North Minahasa District and to determine the inhibiting factor appear in the implementation of progressive tax implementation. The method used in this research is descriptive method that is by collecting data from the results of the research and then analyzing and drawing conclusions from the research. The results obtained that the implementation of progressive tax on motor vehicles in North Minahasa District has been implemented based on existing regulations and taxpayers also have to pay motor vehicle tax based on prevailing rates. However, there are inhibiting factors in the implementation of progressive tax, namely the factor of officers who carry out data collection because often vehicle owners are not in place, facilities and infrastructure factors because not all taxpayers can pay during SAMSAT office hours, the factor of SAMSAT are input errors vehicle owner data, and the factor of the people who are still not aware of the progressive tax rate.Keywords : Motor Vihecle Tax, Progressive Tax, Implementation